Galactic foreground of gamma-ray bursts from AKARI Far-Infrared Surveyor. (22nd November 2018) - Toth, L Viktor; Doi, Yasuo; Zahorecz, Sarolta; Pinter, Sandor; Racz, Istvan I; Bagoly, Zsolt; Balazs, Lajos G; Horvath, Istvan; Kiss, Csaba; Kovács, Tímea; Onishi, Toshikazu
Abstract: We demonstrate the use of the AKARI FIS All-Sky Survey maps in the study of extragalactic objects. A quick but reliable estimate of the Galactic foreground is essential for extragalactic research in general. We explored the galactic foreground and calculated hydrogen column densities using AKARI FIS and other recent all-sky survey data, and compared our results to former estimates. Our AKARI-FIS-based foreground values were then used toward gamma-ray burst (GRB) sources as input for X-ray afterglow spectrum fitting. From those fits the intrinsic column densities at the GRB sources were derived. The high-angular-resolution AKARI-FIS-based Galactic foreground hydrogen column densities are statistically very similar, but for most of the tested directions somewhat lower than previous estimates based on low-resolution data. This is due to the low filling factor of high-density enhancements in all galactic latitudes. Accordingly, our AKARI-FIS-based new intrinsic hydrogen column densities are usually higher or similar compared to the values calculated based, e.g., on the low-resolution Leiden/Argentine/Bonn survey data and listed in the Leicester database. The variation, however, is typically smaller than the error of the estimate from the fits of the X-ray afterglow spectra. There are a number of directions where the improvement of the foreground estimates resulted in an overestimate of magnitude or higher increment of the derived intrinsic hydrogen column densities. We concluded that most of the GRBs with formerly extremely low intrinsic hydrogen column densities are in fact normal, but we confirmed that GRB050233 is indeed a non-enveloped long GRB.